An efficient data routing scheme for multi-patient monitoring in a biomedical sensor network through energy equalization strategy - Chandra, Soumyak; Chandra, Abhijit; Gupta, Rajarshi (Wireless networks, 2021)
Biomedical sensor networks find wide applications in human health monitoring. In such applications, routing strategies in the sensor nodes play a key role towards energy efficiency of the overall system. In this work, we present a new data routing scheme, which is based on residual energy in a node and equalization (named EEQ) among the neighbours to achieve enhanced average node lifetime under short range monitoring scenario. The scheme was hardware implemented using 12 number of indigenous ATmega328 based static biomedical sensor nodes (BSN) arranged in a grid matrix spread over a floor area of 564 sqm. The objective was to collect short duration electrocardiogram and photoplethysmogram signals from human subjects in a local supervisory computer placed outside the grid. Under simulation platform using 100 BSNs with first order radio model, it was found that the average node lifetime was enhanced by 17% against without EEQ evaluated over 10,000 consecutive data collection sessions. The proposed scheme can be useful for providing low cost solution in healthcare settings in developing nations like India.